Pola Komunikasi Interpersonal Dalam Keluarga Poligami Di Desa Sibargot Dusun Padang Rapuan - Linda Yusnidar Ritonga; Faisal Riza; Muhammad Faishal (Lembaga Pengembangan Kinerja Dosen, 2024)
This research was motivated by a topic regarding interpersonal communication patterns in polygamous families in Sibargot Village, Padang Rapuan Hamlet, West Bilah District, Labuhan Batu Regency. The reason for the formation of this research explains, analyzes or details the elements of communication carried out by husband couples with one wife and the other wife, the series of communications between wives, the forms of interaction between children, and the communication barriers faced by polygamous families in Sibargot Village, Padang Rapuan Hamlet. This research uses descriptive qualitative analysis, namely observing and interpreting data found through documents, interviews and observations. The data obtained is first checked for accuracy through data testing techniques. As for analyzing data by selecting, displaying and making conclusions. The results of this research show that the series of communications carried out by husbands to each of their wives does not have a specific communication pattern that occurs in their family, but each family has its own method of managing its two wives. The husband's communication policy is one-way. Then, the two wives used a form of balanced communication interaction between their wives. Things that hinder communication are caused by the lack of time to meet and interact between wives and husbands, resulting in the difficulty of creating a conducive atmosphere in resolving problems which results in many bad perceptions.